PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE BERBAGI PENGETAHUAN SECARA AKTIF DALAM PEMBELAJARAN MATEMATIKA DI KELAS VIII SMP NEGERI 1 X KOTO TANAH DATAR - Shintia Shintia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
In mathematics learning, the active participation of students and the interaction between students and teachers is very important to get good learning outcomes. Based on the results of an initial interview conducted on Monday, August 24, 2015 at 11.00 WIB at SMP Negeri 1 X Koto Tanah Datar, with a mathematics teacher of class VIII SMP Negeri 1 X Koto Tanah Datar (Mrs. Emliati, S.Pd), it was concluded that there were still several constraints in teaching and learning activities. Among them are 1. The level of students 'understanding of the material being taught is still lacking, 2. Students' interest and motivation in learning mathematics is still low, 3. Students tend to be passive in learning, generally do not want to ask the teacher. Even asking friends is reluctant because smart students don't want to share with their friends. So on this occasion, the researcher suggested an appropriate learning strategy, namely the Active Learning Strategy of the Active Knowledge Sharing type. The hypothesis put forward is that the mathematics learning outcomes of students who use Active Learning Strategies of the Type of Active Knowledge Sharing are better than those of students without using Active Learning Strategies of Active Knowledge Sharing types in class VIII of SMP Negeri 1 X Koto Tanah Datar. This type of research is experimental research. The design used is a randomized control group only design. The results of this study are (1) student learning outcomes in the cognitive realm obtained through the test of learning outcomes reached a percentage of completeness of 86.36%, (2) overall student activity is carried out and tends to increase at each meeting, (3) overall teacher activity implemented and tends to increase at every meeting.